The shadow crosser - Cervantes, Jennifer (Cervantes, Jennifer. Storm runner series, 2020)
"When a few Mexica gods try to put their Maya counterparts out of commission, it's up to Zane and some godborns-in-training to save the universe"--Provided by publisher.